Mali : Request for Disbursement under the Rapid Credit Facility-Staff Report; Informational Annex; Staff Statement; Press Release on the Executive Board Approval; and Statement by the Executive Director for Mali. (IMF Staff Country Reports; Country Report ;, 2013)
The security and political crisis in Mali caused a sharp recession along with tax and external financing shortfalls. There has been a sharp expenditure cut and increased recourse to domestic financing, but the accumulation of arrears is prevalent. The first disbursement under the Rapid Credit Facility (RCF) of special drawing rights (SDR) 12 million in February has catalyzed about USD 508 million of budget support thus far. Resumption of donor support brightens the path to economic recovery, but there remain important financing gaps. Strengthening public financial management is essential for sustained macroeconomic and fiscal stability.